Child Marriage within the Sea Tribe of Kelumu Island: Issues and Problems - Winsherly Tan (Jurnal Media Hukum, 2022)
Sea Tribe is a group of indigenous people on Kelumu Island entrenched in the practice of child marriage. This study aims to analyze the law’s implementation on marriage and its impacts on the marine tribal community of Kelumu Island using empirical/socio-legal research methods. Furthermore, the primary legal data used are the 1945 Constitution, Law Number 16 of 2019 concerning Marriage, 35 of 2014, and Law Number 35 of 2014 concerning child protection, and Number 20 of 2003 on Marriage, Child Protection, and National Education System. The Theory of Legal Effectiveness by Soerjono Soekanto was also used. The results showed that the implementation of the marriage law in the Sea Tribe community of Kelumu Island has not yet been classified as adequate. The implementation of the marriage law in the marine tribal community is classified as ineffective when measured by Soerjono Soekanto’s Theory of Legal Effectiveness. This is due to the weakness of several existing factors, namely legal factors, law enforcement, infrastructure, maturity and local communities. Meanwhile, the impact of child marriage is the loss of the children’s right to education and health.